2018
DOI: 10.1128/mra.00818-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Lytic Oenococcus oeni Bacteriophage OE33PA

Abstract: Oenococcus oeni is the most common species of lactic acid bacteria associated with malolactic fermentation in wine. Here, we report the genome sequence of the lytic phage OE33PA (vB_OeS_OE33PA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In the same study, it was shown that the presence of ethanol and low pH values inhibited the phages from attacking the cells, suggesting that inoculation time of the bacterial starters could play a significant role in preventing bacteriophage infections ( Costantini et al, 2017 ). The first sequence of an O. oeni phage, E33PA, has been published in 2018 by Jaomanjaka and co-workers ( Jaomanjaka et al, 2018 ). Interestingly, although most of phage isolated from the Oenococcus genus are temperate, E33PA was found to have a predominately lytic lifestyle ( Jaomanjaka et al, 2018 ).…”
Section: Improvement Of Lab and Technological Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, it was shown that the presence of ethanol and low pH values inhibited the phages from attacking the cells, suggesting that inoculation time of the bacterial starters could play a significant role in preventing bacteriophage infections ( Costantini et al, 2017 ). The first sequence of an O. oeni phage, E33PA, has been published in 2018 by Jaomanjaka and co-workers ( Jaomanjaka et al, 2018 ). Interestingly, although most of phage isolated from the Oenococcus genus are temperate, E33PA was found to have a predominately lytic lifestyle ( Jaomanjaka et al, 2018 ).…”
Section: Improvement Of Lab and Technological Advancesmentioning
confidence: 99%
“…The first sequence of an O. oeni phage, E33PA, has been published in 2018 by Jaomanjaka and co-workers ( Jaomanjaka et al, 2018 ). Interestingly, although most of phage isolated from the Oenococcus genus are temperate, E33PA was found to have a predominately lytic lifestyle ( Jaomanjaka et al, 2018 ).…”
Section: Improvement Of Lab and Technological Advancesmentioning
confidence: 99%
“…To test this, RGJ agar plates were spread in duplicate with serial dilutions of a culture of the sensitive strain IOEBS277. One plate was further air sprayed with the virulent oenophage OE33PA (31,32), while the control was kept uninfected. After incubation, we observed a transition from white to red morphotype for most colonies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oenophages were propagated on strain IOEBS277, which does not contain endogenous phage and is sensitive to all oenophages so far isolated in our laboratory (20,22,31,32). The Lc.…”
Section: Methodsmentioning
confidence: 99%
“…OE33PA is an ex-temperate phage. This virulent mutant harbors an IntB-type integrase sequence [ 21 , 31 ]. Vinitor162 is a professional lytic phage [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%